EVALUSI KONDISI FISIK ATLET BOLAVOLI PANTAI PUSLATDA JAWA TIMUR 2018 - PRAYOGI, ADITYA; , MUHAMMAD (Jurnal Prestasi Olahraga, 2018)
Abstract Beach volleyball is a variation of indoor volleyball which is played by two people in one team, the size of the field is also smaller at 8x16 and sandy, using a really point 2-time win system, the Indonesian beach bolt represented by danang and stars are now in fringe 5 the world in the FIVB Beach Volleyball U19 Word Championship. The purpose of this study was to find out how the physical condition of athletes in Puslatda beach volleyball in East Java. This study uses quantitative methods, then the data obtained in the analysis uses descriptive static. From the results of the components of the physical condition of the beach Bolavoli players who were tested in KONI East Java with the results of the test, the sons Sit and Reach obtained good categories and for the girls were also good, Sons abdominal muscle strength was obtained while the girls were also classified as good, male arm muscle strength (Chin Up) obtained good category while daughter is also classified as good, sons endurance (Beep Test) is obtained in good category while daughter is classified as sufficient, sons speed (Speed) is good and daughter is good, power Vertical jump running son with very good category while the daughter is good. Puslatda beach volleyball athletes in East Java have a good training program as evidenced by the annual, monthly, weekly, and daily training programs equipped with achievement cycles, but there are several aspects of physical conditions that must be corrected and are still quite adequate, VO2Max in athletes the daughter and the category are very good at explosive limb muscle power while the other test items are good. Keywords: Physical condition, Beach Volleyball, athleteAbstrakBolavoli pantai merupakan variasi dari Bolavoli indoor yang dimainkan oleh dua orang dalam satu tim, ukuran lapangan juga lebih kecil yaitu 8x16 dan berpasir, dengan mengunakan sistem really point 2 kali kemenangan, Bolavoli pantai indonesia yang diwakili danang dan bintang kini berada di ringking 5 dunia dalam FIVB Beach Volleyball U19 Word Championship. Tujuan penelitian ini adalah untuk mengetahui bagai mana kondisi fisik atlet Bolavoli pantai Puslatda Jawa Timur. penelitian ini menggunakan metode kuantitatif, kemudian data yang diperoleh di analisis mengunakan statis deskriptif.Dari hasil komponen kondisi fisik pemain Bolavoli pantai yang dilakukan tes di KONI Jawa Timur dengan hasil tes yaitu kelentukan (Sit and Reach) putra diperoleh kategori baik dan untuk putri juga tergolong baik, kekuatan otot perut (Sit Up) Putra diperoleh kategori baik sedangkan putri juga tergolong baik, kekuatan otot lengan (Chin Up) putra diperoleh kategori baik sedangkan putri juga tergolong baik, daya tahan ( Beep Test) putra diperoleh ketegori baik sedangkan putri tergolong cukup, kecepatan (Speed) putra dengan kategori baik dan untuk putri tergolong baik, daya ledak otot tungkai (Vertical jump running) putra dengan kategori baik sekali sedangkan putri tergolong baik. Kesimpulan atlet Bolavoli pantai Puslatda Jawa Timur memiliki progam latihan yang baik ini terbukti dengan adanya progam latihan tahunan,bulanan, mingguan, dan harian dilengkapi dengan siklus pemuncakan prestasi, namun ada beberapa aspek kondisi fisik yang harus diperbaiki dan masih tergolong cukup yaitu VO2Max pada atlet putri dan kategori sangat baik pada daya ledak otot tungkai putra sedangkan item tes yang lain tergolong baik. Kata Kunci : kondisi Fisik, Bolavoli Pantai, atlet